Gallium-incorporated TiO2 thin films by atomic layer deposition for future electronic devices - Sun, Qingxuan; Lin, Yingzhen; Han, Chaoya; Yang, Ze; Li, Ying; Zeng, Yuping; Yang, Weifeng; Zhang, Jie (Frontiers in Materials, 2024)
In this work, we studied the impact of gallium incorporation on electrical and material characteristics of TiO2 thin films. These TiO2 and TiXGaO films with thickness of 15 nm were derived by atomic layer deposition (ALD) and then annealed in O2 ambient at 500 ℃, where the levels of Ga incorporation were tuned by the cycle ratio (X) of TiO2 to that of Ga2O3 during ALD growth. Both thin film transistors (TFTs) using TiXGaO (TiO2) thin films as the channel and metal-oxide semiconductor capacitors (MOSCAPs) using TiXGaO (TiO2) thin films as the dielectric were fabricated to unravel the impact of Ga incorporation on electrical properties of TiO2 thin films. It is found that the Ga incorporation reduces the conductivity of TiO2 thin films significantly. Pure TiO2 thin films could be the ideal channel material for TFTs with excellent switching behaviors whereas Ga-incorporated TiO2 thin films could be the dielectric material for MOSCAPs with good insulating properties. The leakage current and dielectric constant (k) value are also found to be decreased with the increased Ga content in TiXGaO/Si MOSCAPs. Additionally, the density of interface trap (Dit) between TiXGaO and Si were extracted by multi-frequency conductance method, where a "U-shape" trap profile with similar level of Dit values can be observed for TiXGaO MOSCAPs with varying Ga contents. Material characterizations show that the Ga incorporation destabilizes the crystallization and enlarges the bandgap (Eg) of TiO2 while maintaining a smooth surface. Interestingly, Ga incorporation is found to decrease the overall oxygen content and introduce more oxygen-related defects in the film. As a result, the reduction of leakage current upon Ga incorporation in MOSCAPs could be explained by amorphization of the film and enlarged band offset to Si rather than oxygen defect passivation. These Ga-incorporated TiO2 films may found promising usage in future electronic device applications such as trench capacitors in dynamic random-access memory, where the emerging high-k dielectrics with low leakage currents and high thermal stability are demanded.